Tillandsia religiosa, a new species from the state of Morelos, México - Hernández-Cárdenas, Rodrigo; González-Rocha, Edith; Espejo-Serna, Adolfo; López-Ferrari, Ana Rosa; Cerros-Tlatilpa, Rosa; Ehlers, Renate (Phytotaxa, 2014)
Tillandsia religiosa Hern.-Cárdenas, González-Rocha, Espejo, López-Ferr., Cerros & Ehlers, a new species from Morelos, Mexico is described and illustrated. The new species is compared to taxa with similar characteristics, T. taxcoensis Ehlers, T. thyrsigera E. Morren ex Baker and T. superinsignis Matuda. Images and a distribution map of the new taxon are included.